EFFECTS OF HYDRATION ON SCINTIGRAPHIC GLOMERULAR FILTRATION RATE MEASURED USING INTEGRAL AND PLASMA VOLUME METHODS IN DOGS WITH SUSPECTED RENAL DISEASE. Issue 6 (19th May 2014) - Westgren, Frida; Ley, Charles J.; Kampa, Naruepon; Lord, Peter
<x xml:space="preserve">Abstract</x> The current standard scintigraphic method for estimating glomerular filtration rate (GFR) in dogs is the integral method, which normalizes renal GFR to body weight. The plasma volume method, that is normalizing GFR to plasma volume, has been reported to be more physiologically correct. The aim of this prospective study was to test the effect of hydration status on GFR measured by these two methods in a group of dogs with suspected renal disease. Eleven dogs were recruited. All dogs underwent standardized scintigraphic examinations before and after 15 ml/kg of fluid was administered intravenously at 5–7 ml/kg/min. Individual kidney GFR estimates (n = 22) were calculated using both methods and a consensus of two observers who were unaware of clinical findings. Individual kidney GFR increased significantly (P = 0.0008) after fluid administration using the integral method and individual kidney GFR using the plasma volume method remained constant. Percentage differences for individual kidney GFR before and after fluid administration were 31.4 ± 58.1% (change ± 95% CI) for the integral method and 0.1 ± 70% (change ± 95% CI) for the plasma volume method. Intravenously administered fluid increased individual kidney GFR from low to normal in 10 of 22 kidneys using the integral method and in 1 of 22 kidneys using the plasma volume method. Findings supported the use of the plasma volume method for scintigraphic calculation of GFR in dogs with suspected renal disease and indicated that errors of kidney status classification may more likely occur when the integral method is used.